2021
DOI: 10.1007/s11695-021-05605-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Gastrointestinal Symptoms Two To Four Years After Bariatric Surgery. A Cross-Sectional Study Comparing Roux-en-Y Gastric Bypass and Laparoscopic Sleeve Gastrectomy

Abstract: Background Roux-en-Y gastric bypass (RYGBP) and laparoscopic sleeve gastrectomy (LSG) are efficient methods for weight loss (WL) and WL maintenance in severe obesity. However, the knowledge of gastrointestinal (GI) symptoms after surgery is limited. This study aimed to compare the severity of GI symptoms, pain, and self-rated health 2 to 4 years after RYGBP and LSG surgery. Methods In this cross-sectional study, RYGBP and LSG patients answered a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
3
1
0
Order By: Relevance
“…Patients between the ages of 25 and 35 reported the highest prevalence of heartburn symptoms, followed by those between the ages of 36 and 45 and those older than 45. This conclusion is consistent with prior research indicating that younger individuals who undergo SG have an increased likelihood of experiencing heartburn symptoms [ 20 - 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Patients between the ages of 25 and 35 reported the highest prevalence of heartburn symptoms, followed by those between the ages of 36 and 45 and those older than 45. This conclusion is consistent with prior research indicating that younger individuals who undergo SG have an increased likelihood of experiencing heartburn symptoms [ 20 - 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that patients may develop gastrointestinal, musculoskeletal/neurological, mental, and other chronic complications following surgery. Consistent with prior research [20][21][22][23][24] indicating a high prevalence of gastrointestinal symptoms following gastric sleeve surgery, a substantial proportion of patients reported experiencing GERD, dyspepsia, regurgitation, nausea, abdominal discomfort, and abdominal distension. GERD is characterized by the reflux of stomach contents into the esophagus [25].…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with Kvehaugen et al [25] we found only minor reductions of food tolerance after bariatric surgery, with no differences between groups for the overall food tolerance. The current study also supports and extends the main findings of a cross-sectional study comparing RYGB with SG 2 to 4 y after surgery, showing similar gastrointestinal symptom scores (except for reflux) between groups [46]. The current RCT showed no substantial changes in abdominal pain, indigestion, constipation, and diarrhea after either surgery.…”
Section: Food Tolerance Hedonic Hunger Binge Eating Gastrointestinal ...supporting
confidence: 88%